Language Test Item Analysis Techniques : Teknik Analisis Item Tes Bahasa - Najmalia Fitra; Herdah Herdah; Amira Ezzat Mahrous (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
The quality of a learning outcome exam is heavily influenced by the quality of its items, hence it is vital to assess the test items to enhance its quality. Language learning is a complicated learning process that involves four skills: listening, speaking, writing, and reading. The challenge in this study is determining which tactics are used to assess language examinations and how to use them. The research methodology used is library research, which entails acquiring data from a variety of scientific journals for the study. The study's findings suggest that test items may be analyzed in two ways: qualitatively and quantitatively. In qualitative analysis, four variables are considered: material analysis, question creation analysis, cultural/language analysis, and test accuracy about student ability. In addition, quantitative research looks at the test's internal properties, such as test validity, reliability, difficulty level, test item discrimination power, and distractor function efficacy. Keywords: Analysis Techniques, Language, Test Items.